A TILLING Resource for Hard Red Winter Wheat Variety Jagger. Issue 4 (1st July 2019) - Rawat, Nidhi; Joshi, Anupama; Pumphrey, Michael; Singh, Lovepreet; Mahlandt, Alex; Chhabra, Bhavit; Wilson, Duane; Gill, Bikram; Poland, Jesse; Tiwari, Vijay
ABSTRACT: Genetic improvement of crop plants is dependent on the availability of genetic variation, which can be present naturally or can be created using mutations. Ethyl methanesulfonate (EMS) mutagenesis provides an attractive tool to create variant alleles of genes of interest in any plant. In the present paper, we report development of an EMS‐mutagenized population in a hard red winter wheat ( Triticum aestivum L.) variety Jagger. Jagger has been a leading variety across the United States and has been grown internationally as well, for over two decades now. It possesses many useful traits related to disease resistance, cold tolerance, and milling and baking qualities. Because it is a landmark variety, the genome of Jagger is being sequenced by an international collaborative team, which will speed up gene mapping and cloning efforts in it. The Jagger Targeting Induced Local Lesions In Genome (TILLING) resource developed in this work will be useful for functional validation of these genes. The mutagenized population was developed using EMS and was characterized phenotypically and genotypically. Gene‐wise mutation screening was performed for three genes located on different chromosomes across all the three genomes. The population has an overall mutation frequency of 1/40.7 kb, and we were able to find multiple knockout, missense, and missplicing mutations for each targeted gene. The population will be useful as a forward and reverse genetic screen for a number of valuable traits.